2019
DOI: 10.1038/s41598-019-51661-4
|View full text |Cite
|
Sign up to set email alerts
|

Allergic rhinitis is a risk factor of gastro-esophageal reflux disease regardless of the presence of asthma

Abstract: Gastroesophageal reflux disease (GERD) can cause several upper airway symptoms and alter the physiology of nasopharyngeal mucosa, while upper airway diseases in turn might also exacerbate GERD symptoms. For a long time, asthma was considered a risk factor of GERD in the literature. Asthma and allergic rhinitis (AR) are usually identified as united airway disease according to similar epidemiology and pathophysiology; however, the association between AR and GERD is less elucidated. We aimed to evaluate whether A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 24 publications
4
10
0
1
Order By: Relevance
“…We found in our study that LPR and AR occurred simultaneously more frequently as having LPR increased the incidence for AR by more than two folds which is similar to other studies [17,18]. Having asthma increased the correlation, but the correlation persisted even when excluding asthma which concurs with another study [18]. We also found that subjects with asthma had higher LPR and AR symptom scores which are similar to the study [18].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…We found in our study that LPR and AR occurred simultaneously more frequently as having LPR increased the incidence for AR by more than two folds which is similar to other studies [17,18]. Having asthma increased the correlation, but the correlation persisted even when excluding asthma which concurs with another study [18]. We also found that subjects with asthma had higher LPR and AR symptom scores which are similar to the study [18].…”
Section: Discussionsupporting
confidence: 91%
“…A causal link between GORD and AR was not established and only a few studies indicated a correlation [42]. We found in our study that LPR and AR occurred simultaneously more frequently as having LPR increased the incidence for AR by more than two folds which is similar to other studies [17,18]. Having asthma increased the correlation, but the correlation persisted even when excluding asthma which concurs with another study [18].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations